1996
DOI: 10.1002/(sici)1097-0142(19960701)78:1<183::aid-cncr31>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Author reply

Abstract: e have read Foote et al.' with interest. Certainly a W modern series showing the efficacy of 6 megavolt (MY) photon therapy in the treatment of early glottic cancer is reassuring but it is important to note the effect of fraction size. Updated data regarding treatment with 6 MV linear accelerators2 reveals that 22 T1 glottic cancer patients have now been treated with 2.25 gray (Gy) fractions to 63 Gy with 95% 2-year local control (Foote RL, personal communication, 1996). Isn't it possible that the prescription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Clinical trials so far have only shown no or slight improvement in survival. Although a small case series from Mayo Clinic demonstrated the beneficial potential of aggressive multimodal therapy [144], further prospective trials with multimodal or multitarget approach should be performed in hopes of improving the clinical outcome of ATC. Lastly, emerging targets and approaches can not only provide better understanding of the tumor biology but also more optimistic outcome in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials so far have only shown no or slight improvement in survival. Although a small case series from Mayo Clinic demonstrated the beneficial potential of aggressive multimodal therapy [144], further prospective trials with multimodal or multitarget approach should be performed in hopes of improving the clinical outcome of ATC. Lastly, emerging targets and approaches can not only provide better understanding of the tumor biology but also more optimistic outcome in the future.…”
Section: Discussionmentioning
confidence: 99%